Investigation of the Oxidative Stability of Li-Ion Battery Electrolytes Using Cathode Materials. (1st January 2015) - Hofmann, Andreas; Werth, Felix; Höweling, Andres; Hanemann, Thomas
Abstract : In this study, anodic oxidation limits of Li-ion cell electrolytes are investigated against cathode materials containing various metal ions. These results are compared with inactive cell materials (PVDF/carbon black) and Pt working electrodes. The oxidative stability limits are extracted from galvanostatic cycling tests at low C-rates of (∼C/100) which can be used as a measure for electrolyte decomposition limits. It is found that inactive cathode materials affect significantly the anodic decomposition limit of the electrolyte. Therefore such electrode materials can be used instead of inactive electrodes (Pt, stainless steel or glassy carbon) to investigate anodic electrolyte potential limits more reliable.